ORTHODOXY IN ISLMAIC BOARDING SCHOOL INTERPRETATION: Tradisonalist Discorse In The Interpretation Of Al-Bayan Fi Ma’rifati Ma’ani Al-Qur’an By KH. Shodiq Hamzah - Anam, Saichul; Nur Imam Akhmad Yani (UIN Mataram, 2025)
he purpose of this writing is to examine the orthodoxy perspective in the Al-Bayan Fi Ma’rifati Ma’ani Alquran commentary written by KH Shodiq Hamzah from Semarang. Shodiq Hamzah is an intellectual figure in the pesantren community, holding a prominent position within the societal system. The conclusion is based on the fact that this commentary was written at the request of the hajj congregation he led, and his position as a spiritual guide (mursyid) in the Thariqah order. As a pesantren scholar, the tradition in pesantren education, which consistently strives to maintain the orthodoxy of religious teachings through an intellectual network (sanad), is abstracted in his commentary. The